Experimental investigations on high-precision microcutting of copper foils with microfabricated silicon punches - Hildering, Sven; Becsi, L.; Engel, Ulf; Merklein, Marion; Mescheder, U. (Proc. 12th Int. Conf. European Society for Precision Engineering and Nanotechnology, 2012)
The miniaturisation of metallic parts is considerable in various industrial sectors. This trend leads to a demand for decreasing tool dimensions. This study shows the application of monocrystalline silicon as tool material for etched punches used for microcutting of thin copper foils, as etching is a common method in microsystems technology for the economical fabrication of thin vertical structures with a high surface quality. Cutting experiments in a specially designed test rig show the applicability of silicon for microcutting of copper foils and the effect of tool wear on the punching force. The workpiece quality is characterised by a large burnish area of the sheared edges.
LFT Import::2019-08-05 (1804)